2019
DOI: 10.1155/2019/5953618
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Primary Testicular Lymphoma Presenting with Direct Spread along the Spermatic Cord and Gonadal Vessels

Abstract: Primary testicular lymphoma is a rare testicular neoplasm that mainly affects elderly patients, with Human Immunodeficiency Virus (HIV) being a known risk factor in the younger population. Approximately 20% of patients will have disseminated disease with extra-nodal involvement at clinical presentation. Rarely, direct spread along the spermatic cord and gonadal vessels can occur and has been described in the literature. We present two cases of this phenomenon where the primary testicular tumour has spread alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The most important finding in our case which sets it apart from those previously described is the contiguous involvement of spermatic cord and gonadal vein in the form of homogenously enhancing soft tissue extending along these structures on the left side. This finding has been described so far in only a few case reports in the available literature [4] , [5] , [6] .…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The most important finding in our case which sets it apart from those previously described is the contiguous involvement of spermatic cord and gonadal vein in the form of homogenously enhancing soft tissue extending along these structures on the left side. This finding has been described so far in only a few case reports in the available literature [4] , [5] , [6] .…”
Section: Discussionmentioning
confidence: 54%
“…This feature of contiguous spread of tumor along the spermatic cord and gonadal vein described in our case of Primary TNHL can serve as an important distinction between the two; as this is not a feature of secondary involvement in widespread NHL [4] , [5] , [6] . Only a few case reports exist so far detailing the feature of contiguous tumor spread along the spermatic cord and gonadal vein as a pathognomic feature of Primary TNHL [4] , [5] , [6] . Sabale et al [4] described 2 cases of Primary TNHL that showed extension of soft tissue along epididymis and spermatic cord into inguinal canal with further continuous extension along the gonadal vein up to inferior vena cava.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Several case reports have shown a direct spread of PTL along the spermatic cord and gonadal vessels, and this has been proposed to be unique to PTL and not reported in other more common testicular tumors. [ 8 9 10 ] On CT, this is seen as contiguous abnormal soft tissue extending along the spermatic cord and the gonadal vessels, through the inguinal canal, and the retroperitoneum, to the level of insertion of the gonadal veins. [ 8 9 10 ] FDG PET/CT although has limited value in initial diagnosis and differentiation of PTL from other primary testicular neoplasms, it is the imaging modality of choice for identifying extratesticular involvement and staging/restaging of PTL.…”
mentioning
confidence: 99%